Session 2: What causes liver metastases – lymph nodes or is it something else?. (May 2018) - Siddiqui, M.; Nagtegaal, I.; Santiago, I.; Knijn, N.; Berho, M.; Mirnezami, A.; Rao, S.; Brown, G.
Abstract: The traditional view of progression of disease in cancer is the sequential spread of tumour to locoregional lymph nodes and then to distant metastases. However, this view may need to be challenged and modern pathology techniques such as immunohistochemistry and tumour profiling can provide us with a greater insight into the pathways and mechanisms of distant spread. Professor Nagtegaal discusses the evidence for reconsidering the current paradigm and reflects on the need for further investigation into mechanisms of distant metastatic spread.